2013
DOI: 10.7567/jjap.52.08jj06
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Luminescence of Nitrides under Electron-Beam Irradiation

Abstract: The aim of the work was to study the nature of unstable luminescence of nitride bulk layers and heterostructures under stationery electron beam irradiation. During irradiation increasing of intensity of luminescence was observed. Typical times of this effect are tens up to hundreds of seconds. Details of the effect were studied. It was noticed that in several cases the irradiated by electron beam area was characterized by different luminescence properties even after 24 h at room temperature in vacuum. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Two possible mechanisms of such degradation to be considered are (a) the dislocation movement and multiplication caused by recombination of excess charge carriers [so called recombination enhanced dislocation glide (REDG)] 14,15) and (b) impurity diffusion and precipitation on dislocations. 16,17) As an indication of such processes in InGaN=GaN multiple quantum well structures a prominent optical properties modification under low energy electron beam irradiation (LEEBI) [18][19][20][21][22][23][24][25][26][27] can be considered. REDG can be observed by irradiation of samples under study by optical or electron beams [radiation enhanced dislocation glide (REDG)].…”
Section: Introductionmentioning
confidence: 99%
“…Two possible mechanisms of such degradation to be considered are (a) the dislocation movement and multiplication caused by recombination of excess charge carriers [so called recombination enhanced dislocation glide (REDG)] 14,15) and (b) impurity diffusion and precipitation on dislocations. 16,17) As an indication of such processes in InGaN=GaN multiple quantum well structures a prominent optical properties modification under low energy electron beam irradiation (LEEBI) [18][19][20][21][22][23][24][25][26][27] can be considered. REDG can be observed by irradiation of samples under study by optical or electron beams [radiation enhanced dislocation glide (REDG)].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these devices have strong radiation resistance, which is expected to be used in space systems. Therefore, it is important to study the influence of high-energy irradiation on GaN-based devices [5][6][7][8][9]. The results show that GaN-based devices have high sensitivity to relatively low-dose gamma ray, electron, proton, and neutron irradiation [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…[1]). The effects of low energy electron beam irradiation (LEEBI) on optical properties of InGaN/GaN structures with multiple quantum wells (MQW) have been studied in numerous papers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] because this point is important not only for the adequate characterization of such structures by the SEM methods but also for evaluating the light emitting diodes (LEDs) stability under prolonged high forward current, photon or electron beam injection. It was observed that LEEBI leads to an essential increase in the cathodoluminescence (CL) intensity (by more than two orders of magnitude in some structures [2] ) and to a blue shift of MQW-related emission band.…”
Section: Introductionmentioning
confidence: 99%
“…This strain produces a piezoelectric polarization field, which can exceed 1 MV cm À1 [18] that in turn decreases the QW emission energy due to the quantum-confined Stark effect (QCSE). Therefore, in the majority of papers the LEEBI effect was explained by a partial compensation of piezoelectric polarization field due to the recharging of surface and/or interface states [2,8,13] or by the activation of donors and/or acceptors screening the electric field in the QWs. [3] Of course, such effects can take place, moreover, some results confirming the surface effect were obtained in Ref.…”
Section: Introductionmentioning
confidence: 99%